Biological and biochemical effects of lufenuron on Xanthogaleruca luteola (Muller, 1766 ) (Coleoptera: Chrysomelidae) - Bahareh MOHAMMADZADEH TAMAM; Mohammad GHADAMYARI; Elaheh SHAFIEI ALAVIJEH (Acta Agriculturae Slovenica, 2022)
Xanthogaleruca luteola (Mull., 1766) is the major defoliator pest of elm trees in urban area. In this study the effect of lufenuron on some biochemical and biological characteristics was investigated on X. luteola. The LC30 and LC50 of lufenuron were determined on the second instar larvae as 20.22 and 36.65 mg l-1, respectively. Effects of LC30 and LC50 concentrations of lufenuron on some biological parameters showed that lufenuron caused an increase in larval, pre-pupal and pupal developmental periods. Also, none of the female insects that emerged from the treated larvae did not spawn during their life. The LC50 concentration of lufenuron decreased carbohydrate, lipid and protein content and increased glycogen content. But there was not a significant difference in glycogen, and protein contents following the exposure to LC30 concentration. However, glutathione-s-transferase (GST) and esterase activities were significantly increased at LC50. In conclusion, due to lethal and sublethal effect of lufenuron on biochemical and biological traits of X. luteola, it can be recommended for control this pest in IPM program.